Coupling a peatland hydrological model with a snowmelt module in order to model the snowmelt runoff in a boreal ombrotrophic peatland in eastern Québec (Canada) - Riahi, Khawla; St-Hilaire, André; Bourgault, Marc-André; Taillardat, Pierre; Prijac, Antonin; Garneau, Michelle (Canadian Journal of Civil Engineering, 2024)
Peatlands are relatively common in the province of Quebec (Canada) where they occupy about 12% of the surface. The hydrology of peatlands remains insufficiently documented, more specifically during the spring period where data are currently lacking in many regions, including in the Quebec boreal territory. The paucity of spring data are due to snowmelt that causes flooding in peatlands and along rivers, which makes hydrometry complicated during this period of the year. In this paper, the Peatland Hydrological Impact Model (PHIM) was coupled with a snowmelt module (CemaNeige) to simulate spring flows in an ombrotrophic peatland located in the Romaine River watershed (Quebec). Discharge data from two summer seasons (2019 and 2020) were used to calibrate the hydrological model. Despite the relatively short time series, the results show a good performance. The simulated spring flows resulting from the PHIM + CemaNeige combination are of the right order of magnitude.
Keywords: Infolettre; Infolettre_Fevrier_2025